Association between diabetes at different diagnostic ages and risk of cancer incidence and mortality: a cohort study - Peng, Yu; Liu, Fubin; Wang, Peng; Qiao, Yating; Si, Changyu; Wang, Xixuan; Gong, Jianxiao; Zhou, Huijun; Song, Fengju; Song, Fangfang (Frontiers in Endocrinology, 2023)
Background: Different ages for diagnosis of diabetes have diverse effects on risks of cardiovascular disease, dementia, mortality, but there is little evidence of cancer. This study investigated the relationship between diabetes at different diagnostic ages and risks of cancer incidence and mortality in people aged 37-73 years. Methods: Participants with diabetes in the UK Biobank prospective cohort were divided into four groups: ≤40, 41-50, 51-60, >60 according to age at diagnosis. A total of 26,318 diabetics and 105,272 controls (1:4 randomly selected for each diabetic matched by the same baseline age) were included. We calculated the incidence density, standardized incidence and mortality rates of cancer. Cox proportional hazards model was used to examine the associations of diabetes at different diagnostic ages with cancer incidence and mortality, followed by subgroup analyses. Results: Compared to corresponding controls, standardized incidence and mortality rates of overall and digestive system cancers were higher in diabetes diagnosed at age 41-50, 51-60, and >60 years, especially at 51-60 years. Individuals diagnosed with diabetes at different ages were at higher risk to develop site-specific cancers, with a prominently increased risk of liver cancer since the diagnosis age of >40 years. Significantly, participants with diabetes diagnosed at 51-60 years was correlated with various site-specific cancers risks (HR for incidence: 1.088-2.416, HR for mortality: 1.276-3.269). Moreover, for mortality of digestive system cancers, we observed an interaction effect between smoking and diabetes diagnosed at 51-60 years. Conclusion: Our findings highlighted that the age at diagnosis of diabetes, especially 51-60 years was critical risks of cancer incidence and mortality and may represent a potential preventative window for cancer.